2015
DOI: 10.1016/j.nicl.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Measuring longitudinal myelin water fraction in new multiple sclerosis lesions

Abstract: ObjectivesInvestigating the potential of myelin repair strategies in multiple sclerosis (MS) requires an understanding of myelin dynamics during lesion evolution. The objective of this study is to longitudinally measure myelin water fraction (MWF), an MRI biomarker of myelin, in new MS lesions and to identify factors that influence their subsequent myelin content.MethodsTwenty-three MS patients were scanned with whole-brain Fast Acquisition with Spiral Trajectory and T2prep (FAST-T2) MWF mapping at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 46 publications
(55 reference statements)
2
40
2
Order By: Relevance
“…For quantitative assessment of tissue damage in white matter MS lesions, MWF is regarded as an indirect measure of myelin with a relatively high specificity given the strong pathological correlation. 2628 We recognize that an increase susceptibility within a chronic lesion can be due to demyelination or iron deposition, which limits direct iron quantification by QSM. 17 We identify QSM rim+ lesions as having a rim of iron based upon the susceptibility gradient between the rim and core regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quantitative assessment of tissue damage in white matter MS lesions, MWF is regarded as an indirect measure of myelin with a relatively high specificity given the strong pathological correlation. 2628 We recognize that an increase susceptibility within a chronic lesion can be due to demyelination or iron deposition, which limits direct iron quantification by QSM. 17 We identify QSM rim+ lesions as having a rim of iron based upon the susceptibility gradient between the rim and core regions.…”
Section: Discussionmentioning
confidence: 99%
“…MWF is a well-validated quantitative MRI biomarker for myelin, 26, 27 which can be mapped efficiently and reproducibly with FAST-T2. 25, 28 The QSM0 algorithm improves QSM zero reference selection by enforcing susceptibility homogeneity of CSF within the brain ventricles and eliminating the need for manual drawing of CSF region-of-interest (ROI). QSM0 and MWF were used to identify MS lesions with a hyperintense rim pattern consistent with iron deposition and to assess the extent of myelin damage found within these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…mcDESPOT-derived MWF shows a positive correlation between physical activity level and MWF in the right parahippocampal cingulum (16) and one study found regional differences in MWF of the corpus callosum between males and females (91). Reproducibility and reliability of MWF in healthy controls, both at a single site and multiple sites is very good (14,103,171,174).…”
Section: In Vivo Applications Of Myelin Water Imaging In Research Andmentioning
confidence: 99%
“…Myelin water fraction (MWF), defined as the fraction of the total signal which has T 2 < 40 milliseconds at 3 Tesla, has been histologically validated as a marker of myelin density in human tissue, 30–32 and has good scan‐rescan reproducibility (coefficient of variation 4% in cerebral white matter) 33 . MWI has been used to investigate myelin in a wide range of diseases including multiple sclerosis, neuromyelitis optica spectrum disorder, schizophrenia, Niemann‐Pick disease, prenatal alcohol exposure, amyotrophic and primary lateral sclerosis, Krabbe disease, autism, stroke, and traumatic brain injury 34–47 . Rapid myelination has been demonstrated in early childhood and adolescence using multicomponent driven equilibrium single pulse observation of T 1 and T 2 (mcDESPOT), an alternate approach to MWI using a steady‐state acquisition 48–53 .…”
Section: Introductionmentioning
confidence: 99%
“…33 MWI has been used to investigate myelin in a wide range of diseases including multiple sclerosis, neuromyelitis optica spectrum disorder, schizophrenia, Niemann-Pick disease, prenatal alcohol exposure, amyotrophic and primary lateral sclerosis, Krabbe disease, autism, stroke, and traumatic brain injury. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] Rapid myelination has been demonstrated in early childhood and adolescence using multicomponent driven equilibrium single pulse observation of T 1 and T 2 (mcDESPOT), an alternate approach to MWI using a steadystate acquisition. [48][49][50][51][52][53] Adult multi-echo T 2 -based MWF atlases in both brain and cervical spinal cord have recently been published, 54,55 but, to our knowledge, no such atlases exist for children.…”
Section: Introductionmentioning
confidence: 99%